Action Needed Now To Urge Major Increase In Federal Tobacco Tax (Tufts Archival Research Center, 2007)
Publication calling for action from supporters of President Clinton's proposed cigarette tax increase. Encourages supporters to write letters, fax and make phone calls to both the Clinton Administration and local politicians. Lists key points for supporters to include in their efforts and provides a sample letter, as well as contact information for national and state level politicians.